Mammary-Type Myofibroblastoma: A Report of Two Cases - Soyeon An; Joon Seon Song; Soonchan Park; Jung Won Lee; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Mammary-type myofibroblastoma (MFB) is a rare, benign spindle cell neoplasm occurring along the milkline, with extension from the mid-axilla to the medial groin. It is histologically and immunohistochemically identical to MFB of the breast and is part of a spectrum of lesions that includes spindle cell lipoma and cellular angiofibroma. Recently, we experienced two cases of mammary-type MFB involving male patients aged 30 and 58 years, respectively. The tumors were located in the right scrotal sac and in the right axilla. Wide excisions were performed. Microscopically, the masses were composed of haphazardly arranged, variably sized fascicles of bland spindle cells and were admixed with mature fat tissue. The spindle cells in both cases showed immunopositivity for desmin and CD34 and negativity for smooth muscle actin. Loss of retinoblastoma (RB)/13q14 loci is a characteristic genetic alteration of mammary-type MFB, and we identified loss of RB protein expression by immunohistochemical staining. We emphasize the importance of awareness of this rare neoplasm when a spindle cell neoplasm is accompanied by desmin immunopositivity. The second patient was alive without recurrence for 20 months, and the first patient had not been followed.